Maslinic Acid Ameliorates Inflammation via the Downregulation of NF-κB and STAT-1 - Wonhwa Lee; Jaehong Kim; Eui Kyun Park; Jong-Sup Bae (MDPI AG, 2020)
Maslinic acid (MA), a natural compound of the triterpenoid group derived from olive, prevents the generation of pro-inflammatory cytokines and oxidative stress. In human umbilical vein endothelial cells (HUVECs) treated with lipopolysaccharide (LPS), we characterized the effects of MA on the regulation of heme oxygenase (HO)-1, cyclooxygenase (COX-)2, and inducible nitric oxide synthase (iNOS). MA was tested in the lung tissues of LPS-treated mice, to determine its effect on levels of iNOS expression and representative inflammatory mediators such as interleukin (IL)-1α and tumor necrosis factor (TNF)-α. We show that MA induced the expression of HO-1, reduced LPS-induced NF-κB-luciferase activity, and inhibited iNOS/NO and COX-2/PGE2, resulting in the downregulation of STAT-1 phosphorylation. Furthermore, our data show that MA induced the nuclear translocation of Nrf2, increased the binding of Nrf2 to ARE, and decreased IL-1α production in LPS-treated HUVECs. The MA-induced reduction in iNOS/NO expression was reversed by RNAi suppression of HO-1. In mice treated with LPS, MA significantly downregulated levels of iNOS in lung tissue and TNF-α in the bronchoalveolar lavage fluid. Taken together, our findings indicate that MA exerts a critical anti-inflammatory effect by modulating iNOS via the downregulation of NF-κB and p-STAT-1. Thus, we propose that MA may be an ideal substance to treat inflammatory diseases.